2020
DOI: 10.3390/ijerph17186892
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Perceptions about Cervical Cancer Risk, Prevention and Human Papilloma Virus (HPV) in Vulnerable Women in Greece

Abstract: Cervical cancer can be largely preventable through primary and secondary prevention activities. Following the financial crisis in Greece since 2011 and the increased number of refugees/migrants since 2015 the proportion of vulnerable population groups in Greece increased greatly and the ability of the healthcare sector to respond and to cover the health needs of the population is put under tremendous stress. A cross-sectional study was designed to assess the characteristics of vulnerable women in Greece regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…When considering our screening attitude assessment, both income and education was positively linked to screening attendance and vaccination (more income and better education increased turnout probability). These results were in support of Adjei Boakye et al [ 3 ], Jeudin et al [ 11 ], Marlow [ 4 ] and Riza et al [ 7 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When considering our screening attitude assessment, both income and education was positively linked to screening attendance and vaccination (more income and better education increased turnout probability). These results were in support of Adjei Boakye et al [ 3 ], Jeudin et al [ 11 ], Marlow [ 4 ] and Riza et al [ 7 ].…”
Section: Discussionsupporting
confidence: 86%
“…Besides ethnic affiliation and personal knowledge, religious orientations were also identified as either constraints or enablers of vaccination [ 5 , 6 ]. Riza et al [ 7 ] confirmed that socio-economic background and education were important facilitators of Pap smear testing and HPV vaccination. They argued that Roma ethnic origin was associated with misguided beliefs concerning cervical screening and the HPV vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dedicated prevention protocols should be considered to protect vulnerable populations like female migrants/refugees, considered at higher risk for CC incidence, whereas evidence suggests that women with a migration background of BC tend to acquire the same exposure risk of and are less likely to participate in mammography screenings than autochthonous women [100][101][102]. In the future, preventive measures should be adopted to limit the burden of incidence and mortality of female cancers and be actively offered to the general population in developed and less developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Besides ethnic a liation and personal knowledge, religious orientations were also identi ed as either constraints or enablers of vaccination (Chaparro et al, 2020, Shelton et al, 2013. Riza et al (2020) con rmed that socio-economic background and education were important facilitators of Pap smear testing and HPV vaccination. They argued that Roma ethnic origin was associated with misguided beliefs concerning cervical screening and the HPV vaccine.…”
Section: Introductionmentioning
confidence: 91%